Synthesis of L-serine modified benzene bridged periodic mesoporous organosilica and its catalytic performance towards aldol condensations - Huybrechts, Ward; Lauwaert, Jeroen; De Vylder, Anton; Mertens, Myrjam; Mali, Gregor; Thybaut, Joris W.; Van Der Voort, Pascal; Cool, Pegie (Microporous and mesoporous materials, 2017)
Periodic mesoporous organosilica materials (PMOs) offer unique possibilities towards catalysis due to their high stability and tunable organic bridges. Moreover, the presence of the organic bridges make them, in comparison with the traditional silica materials, much more robust in an aqueous environment. As a result, these materials can be applied as catalysts for the valorization of biomass-based resources which are, typically, performed in the presence of water. In this work, we post-synthetically modified benzene bridged PMO with L-serine, thus obtaining a bifunctional PMO bearing a primary amine with an alcohol group on the β-carbon. The promoting effect of the alcohol, in combination with the amine as a base catalyst, is beneficial in the aldol condensation of acetone and 4-nitrobenzaldehyde. Thorough characterization, including a solid state NMR study, of the L-serine modified PMO was performed as well as a successful catalytic test in an aqueous environment. We obtained a TOF value of 1.61 × 10−4 ± 0.08 × 10−4 s−1 and a high selectivity towards the aldol product. [Display omitted] •L-serine modified benzene bridged PMO as bifunctional catalyst.•Catalytically tested in the aldol condensation of acetone and 4-nitrobenzaldehyde.•Tested in aqueous environment with high selectivity towards the aldol product.